A novel in-home digital treatment to improve processing speed in people with multiple sclerosis: A pilot study. (April 2021) - Bove, Riley; Rowles, William; Zhao, Chao; Anderson, Annika; Friedman, Samuel; Langdon, Dawn; Alexander, Amber; Sacco, Simone; Henry, Roland; Gazzaley, Adam; Feinstein, Anthony; Anguera, Joaquin A
Objective: To assess whether a videogame-like digital treatment is superior to a control in improving processing speed in adults with multiple sclerosis (MS). Methods: Adults with MS and baseline Symbol Digit Modalities Test (SDMT) z -scores between −2 and 0 were enrolled in a double-blind randomized controlled clinical trial. After completing a baseline in-clinic evaluation (Visit 1), they were randomized to complete an in-home, tablet-based videogame-like digital treatment (AKL-T03) or control word game (AKL-T09) for up to 25 minutes/day, 5 days/week, for 6 weeks. A repeat in-clinic evaluation occurred at 6 weeks (Visit 2), and again 8 weeks later to determine persistence of effects (Visit 3). The pre-specified primary outcome was change in SDMT score between Visits 1 and 2. Results: SDMT increased at Visit 2 for participants randomized to both AKL-T03 ( p  < 0.001) and AKL-T09 ( p  = 0.024). These respective mean improvements were +6.10 and +3.55 (comparison p  = 0.21). At Visit 3, 70% of participants randomized to AKL-T03 maintained a clinically meaningful 4+-point increase in SDMT above their baseline, compared with 37% for AKL-T09 ( p  = 0.038). Conclusion: This in-home digital intervention resulted in substantial and durable improvements in processing speed. A larger randomized controlled clinical trial is planned. Trial Registration: This trial is registered on ClinicalTrials.gov under "NCT03569618, "https://clinicaltrials.gov/ct2/show/NCT03569618 .